Antropologia in vilico: le prospettive di Tommaso d’Aquino e John R. Searle sulla libertà e sulla natura umana - Gallo, Francesco Luigi (Sapientia, 2022)
The construction of anthropological discourse seems to encounter blatantly dilemmatic situations when attempting to hold together, within the same theoretical framework being constructed, theses - at least seemingly - irreconcilable. This 'destiny' of philosophical anthropology appears to render impossible the construction of a theory of the human being that takes into consideration, in an integrated and coherent manner, all the aspects that actually, from an ontological point of view, seem to coexist in humans. Based on this epistemological consideration, this study will analyze two theories as different as they are similar in the destiny that distinguishes them (that is, terminal aporeticism and dilemmatic stasis). John Searle's theory of freedom and Thomas Aquinas's theory of the unity of the human being. Both theories, therefore, despite their irreducible diversity, bear witness to this peculiar characteristic of philosophical anthropology that seems truly condemned either to the formulation of coherent reductionist theoretical frameworks or to complex contradictory and aporetic theories.